2017
DOI: 10.3390/ijms18050970
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Hydroxylated Polybrominated Diphenyl Ethers in Developing Zebrafish Are Indicative of Disruption of Oxidative Phosphorylation

Abstract: Hydroxylated polybrominated diphenyl ethers (OH-PBDEs) have been detected in humans and wildlife. Using in vitro models, we recently showed that OH-PBDEs disrupt oxidative phosphorylation (OXPHOS), an essential process in energy metabolism. The goal of the current study was to determine the in vivo effects of OH-PBDE reported in marine wildlife. To this end, we exposed zebrafish larvae to 17 OH-PBDEs from fertilisation to 6 days of age, and determined developmental toxicity as well as OXPHOS disruption potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Different types of model systems have their own advantages and disadvantages related to multicellular complexity, ease of culture, variability between cultures, possibilities with regard to differentiation or genetic modification, species and costs. Test systems with non-mammalian test organisms [125, 126] may include ecotoxicologically relevant species, or methods to study the neurotoxicity endpoints may be modified to enable an application for other species.…”
Section: In Vitro Eco-neurotoxicity Approachesmentioning
confidence: 99%
“…Different types of model systems have their own advantages and disadvantages related to multicellular complexity, ease of culture, variability between cultures, possibilities with regard to differentiation or genetic modification, species and costs. Test systems with non-mammalian test organisms [125, 126] may include ecotoxicologically relevant species, or methods to study the neurotoxicity endpoints may be modified to enable an application for other species.…”
Section: In Vitro Eco-neurotoxicity Approachesmentioning
confidence: 99%
“…As previously discussed for PS, this may reflect higher energetic cost linked to detoxification and ROS buffering responses, as robust BDE-47 induced oxidative stress has been reported in a variety of species including (developing) zebrafish (Fernie et al, 2005;Shao et al, 2008;Tagliaferri et al, 2010;Costa et al, 2015;Usenko et al, 2015;Meng et al, 2020;Messina et al, 2020). Again, similar to described PS mode of actions, BDE-47 and its hydroxylated metabolite 6-OH BDE-47, have recently been described to decrease mitochondrial OXPHOS gene expression and ATP production and increase oxygen consumption indicative of OXPHOS disruption uncoupling in zebrafish (Legradi et al, 2017;Zhuang et al, 2020), suggesting a mitochondrial contribution to the observed increase in oxygen consumption rate. Like PS, BDE-47 exposure also increased the feeding rate.…”
Section: Individual Ps Nanoplastic and Bde-47 Exposure Induces Organi...mentioning
confidence: 74%
“…Gene expression analysis indicates that 6‐OH‐BDE‐47 affects the procedure of oxidative phosphorylation, suggesting the embryo development hinder may be caused by the disruption of energy production (Peng et al, 2016). The potential influence of energy hemostasis is verified in zebrafish and zebrafish PAC2 cells (Legradi et al, 2014, 2017). Exposure of OH‐PBDEs can increase the consumption of oxygen, which is resulted from the disruption of oxidative phosphorylation via inhibition of electron transport chain and protonophoric uncoupling.…”
Section: Toxicitymentioning
confidence: 97%
“…OH‐PBDEs may disturb thyroid and estrogen hormone hemostasis (Mercado‐Feliciano & Bigsby, 2008; Li et al, 2010), impair neural development (Poston et al, 2018), cause cell toxicity (An et al, 2011; Karpeta & Gregoraszczuk, 2017), induce neurotoxicity (Dingemans, van den Berg, & Westerink, 2011; Roberts, Bianco, & Stapleton, 2015), and transformed to more toxic compounds (Bastos, Eriksson, & Bergman, 2009). Moreover, the potential mechanisms that OH‐PBDEs generate adverse health effects have been illuminated via diverse research (Dingemans et al, 2008, 2010; Macaulay et al, 2015; Legradi et al, 2017; Marchitti et al, 2017; Marsan & Bayse, 2017).…”
Section: Introductionmentioning
confidence: 99%